Death of a discipline? : reflections on the history, state, and future of social anthropology in Zimbabwe - Mawere, Munyaradzi (Langaa RPCIG, 2017)
This is a book on the state of social anthropology as an academic discipline in contemporary Zimbabwe. The authors are frustrated and disheartened by a problematic visibility and sluggish growth of the discipline in the country. The book makes an important claim that the future and vibrancy of anthropology in Zimbabwe, lies in how well anthropologists in the country and in the diaspora are able to join efforts in articulating, debating and enhancing its relevance and vitality. The book provides critical overview and nuanced analyses of the role and continued relevance of the discipline in reading and interpreting the social unfolding of everyday life and dynamism. It is a vital text for understanding and contextualising histories and trends in the development of social anthropology in Zimbabwe and how anthropologists in the country navigate the tumultuous waters and struggles that have engrossed the discipline since colonial times. The book has the capacity to generate added insights and influence national, continental, and global debates and trends in the field.